Handbook of Green Chemistry 2010
DOI: 10.1002/9783527628698.hgc064
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Dissolution and Processing with Ionic Liquids

Abstract: The sections in this article are General Aspects Dissolution of Cellulose in Ionic Liquids Rheological Behavior of Cellulose Solutions in Ionic Liquids Regeneration of the Cellulose and Recycling of the Ionic Liquid Cellulosic Fibers Cellulose Derivatives Fractionation of Biomass with Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The authors studied the stability and spinnability of different commercial dissolving pulps dissolved in [bmim]Cl 2a and [amim]Cl 3a. All solutions were spun according to the NMMO-based Lyocell technique, that is, in a dry-jet wet spinning process where the liquid filament first passes through an air gap before immersion in the coagulation bath where the solid cellulosic fibers are formed [68]. Gel permeation chromatography (GPC) analyses revealed that ILs 2a and 3a degrade the cellulosic solute substantially at 90 and 80 C, respectively.…”
Section: Fiber Spinningmentioning
confidence: 99%
“…The authors studied the stability and spinnability of different commercial dissolving pulps dissolved in [bmim]Cl 2a and [amim]Cl 3a. All solutions were spun according to the NMMO-based Lyocell technique, that is, in a dry-jet wet spinning process where the liquid filament first passes through an air gap before immersion in the coagulation bath where the solid cellulosic fibers are formed [68]. Gel permeation chromatography (GPC) analyses revealed that ILs 2a and 3a degrade the cellulosic solute substantially at 90 and 80 C, respectively.…”
Section: Fiber Spinningmentioning
confidence: 99%
“…The liquid fibers pass through the air gap and then are immersed in a coagulation bath to obtain RCFs. [ 56,57 ]…”
Section: Non‐derivative Organic Solvent Systemsmentioning
confidence: 99%
“…For instance, a solvent with a linear shape can penetrate porogen pores, while a solvent with a branched shape has significantly hindered diffusion into the pores. 96 The solvent's ease of availability, chemical/thermal stability, biocompatibility, low vapour pressure, low melting point, low specific heat, non-corrosiveness, and low viscosity and density are also important considerations depending on the application. 43,96 A solvent with high chain mobility and weak interaction with gas molecules will lead to high diffusion coefficients, which will enable rapid mass transport of gas molecules.…”
Section: Type Imentioning
confidence: 99%
“…96 The solvent's ease of availability, chemical/thermal stability, biocompatibility, low vapour pressure, low melting point, low specific heat, non-corrosiveness, and low viscosity and density are also important considerations depending on the application. 43,96 A solvent with high chain mobility and weak interaction with gas molecules will lead to high diffusion coefficients, which will enable rapid mass transport of gas molecules. 57 Attention must also be paid to solve viscosity, such that the final PL has low viscosity to facilitate both mass transport and handling.…”
Section: Type Imentioning
confidence: 99%